Remarks about Incommensurability in Pedagogical Research - Śleziński, Krzysztof (Przegląd Badań Edukacyjnych (Educational Studies Review), 2018)
There are numerous areas in pedagogical research where incommensurability can occur. It can be the source of many mistakes in the formulation of conclusions coming from the research conducted. The paper discusses some categories of incommensurability, such as epistemological, methodological, social and linguistic ones. Pedagogical investigations are at risk of facing the above-listed categories of incommensurability. In such a case, a pedagogue should be constantly aware of these categories and of their possible occurrence.